Dynamics Interpretation Contemporary in Social Media : Analysis Content Tafsir Education Instagram Account @sekolahtafsir.id - Taufik Warman Mahfuzh; Surahman Amin; Rian Hidayat; Mahda Mahda; Salih Yousif Sharaf (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study examines how Qur'anic sciences and tafsir are represented, simplified, and disseminated through social media, using the Instagram account @bisnistafsir.id as its primary case. A qualitative-descriptive approach was employed, combining library research with digital content analysis. Data were collected through documentation of uploaded content, non-participant observation, and a review of literature on Qur'anic studies and digital media. The findings reveal that @schooltafsir.id successfully merges scholarly authority with popular media formats by using stitched viral videos as an entry point for religious clarification. Its content is concise, structured, and grounded in credible sources classical tafsir books, hadith literature, and academic references allowing it to maintain intellectual rigor within the constraints of short-form media. The account's approach proves effective in translating complex tafsir concepts into accessible insights while correcting widespread religious misinformation in online spaces. Overall, this study concludes that @schooltafsir.id plays a significant role in strengthening digital religious literacy by offering a credible, responsive, and methodologically sound model for presenting Qur'anic knowledge within contemporary social media ecosystems.